MORALĖS MISTIKA - Jokubaitis, Alvydas (Problemos, 2011)
Straipsnio tikslas – išplėtoti Ludwigo Wittgensteino mintį apie mistinius moralės elementus. Tai daroma remiantis Blaise’o Pascalio ir Immanuelio Kanto idėjomis. Pascalis kalbėjo apie meilės fenomeno mistiškumą. Kantas samprotavo apie praktinio proto mistiką. Šių dviejų autorių moralės samprata leidžia kalbėti apie mistinius moralės elementus. Remiantis Pascalio ir Kanto idėjomis, bandoma įrodyti, kad mistika nėra vien religinio mąstymo dalis, bet gali būti traktuojama kaip svarbus moralinio patyrimo elementas.Pagrindiniai žodžiai: moralė, mokslas, mistika, meilė, transcendentalizmas.Mysticism of MoralityAlvydas JokubaitisSummaryThe aim of this article is to develop Wittgenstein’s idea of mystical elements of morality. This is done by invoking the thoughts of Blaise Pascal and Immanuel Kant. Pascal talked about mysticism of love. Kant philosophized about the mysticism of practical reason. The conception of morality developed by these two thinkers allows us to speak about mystical elements of morality. Building on from the ideas of Pascal and Kant one can try to prove that mysticism is not exclusively part of religious mode of thinking but should be treated as important part of moral experience.Science demands the usage of empirical facts. Religious people are mystics, they acknowledge entities that are not describable in scientific terms. Discussions about mysticism do not necessarily have to be based on religion. Scientists cannot accept the proposition “God exists” or “the soul is immortal”, there is no sense in talking about mysticism with them. Another way of defending mysticism looks much more promising – to prove that moral judgement has mystical elements. Ludwig Wittgenstein thought that ethics cannot be expressed in ordinary scientific language but directs towards something that is absolute and mystical.Wittgenstein thought that science is capable of exhausting the entirety of valid propositions. In his opinion, sentences about morality center on things that are absolute, transcending the world of empirical facts. This viewpoint is in agreement with the basic intentions we find in philosophy of morality of Pascal and Kant. Ethical judgement can be interpreted as one of many forms of mystical thinking. Mystical approach to ethics is dislodged to the margins of Western philosophical discourse. This has very much to do with philosophers’ distrust in religion. This article presents arguments, which prove that we can reasonably talk about mysticism of morality.Keywords: mortality, science, mysticism, love, transcendentalism.